Quality Characteristics of Functional Beverages from Moringa Leaf Juice with the Addition of Red Ginger Juice and Sucralose - Julfi Restu Amelia; Bella Roslia Syafitri (The University of Lampung, 2024)
Moringa functional drink is well known for its benefits for health but has weaknesses in the form of sensory value in aroma and taste, so the addition of red ginger juice and sucralose is necessary. The research aims to determine the quality characteristics of functional drink, which is added with varying concentrations of red ginger juice and sucralose and reviewed based on its physical, chemical, microbiological, and organoleptics. Completely Randomized Design (CRD) was used for research design with two factors and two replications: red ginger juice (30%, 40%, and 50%) and sucralose (100 ppm, 150 ppm, and 200 ppm). The ANOVA showed significantly different results (α = 0.05) for total dissolved solids, antioxidant activity values, and organoleptic tests. The best treatment was obtained by adding a concentration of 40% red ginger juice and 150 ppm sucralose, with a total dissolved solids value of 4.97˚Brix, an IC₅₀ antioxidant activity value of 46 ppm indicating very strong antioxidant activity, the hedonic test score was in score range of 4 for color and 5 for aroma and taste. The metals contamination is below the threshold, the total plate number is <1×10³ colonies/ml, and the yeast mold number is <1×10² colonies/ml. Keywords: Antioxidant, Functional, Moringa, Red Ginger, Sucralose.